Smart A.I Mirror - ahnaf, hazieq; Khalid, Izzah; Roslee, Ummi; Sanusi, Hamim (Multidisciplinary Applied Research and Innovation, 2022)
: Smart A.I mirrors are a relatively new addition to the smart product family that has gotten a lot of attention from both commercial producers and amateurs in recent years. [1] This thesis looks towards incorporating intelligence into such mirrors. The Smart A.I Mirror encompasses smart display devices which looks like actual mirror. The objective is to design an innovative mirror prototype that is able to listen to instructions as well as communicate with humans for an instruction to be given while spending long time in front of the mirror before getting ready to work. To construct this smart mirror, the approach must involve an analysis of the smart mirror, the design of hardware and software, the development of a prototype, the implementation, and finally the assessment stages. Weather, time and date, forecast, news, holiday calendar, and complement as inspiration will be displayed on the mirror. Furthermore, our framework includes a LED light presentation that may be used as decoration. The Raspberry Pi 3 board Model B (RPI) will be utilized as the smart mirror's embedded computational unit. Moreover, Voice Assistants (VAs) are computer programmes that answer questions and do activities for users, such as Amazon's Alexa, Google Assistant, Apple's Siri, and Microsoft's Cortana. VAs, also known as virtual assistants, digital assistants, or intelligent personal assistants, represent a change in the way people engage with technology. [2] Users of the Smart Mirror system may easily manage their daily activities as well as solve a variety of difficulties related to household duties.